Post-Traumatic Stress Disorder on the Main Character in “First Love” by Gwendoline Riley - Titi Rahayu Agustin (Morphosis: Journal of Literature, 2024)
This study aims to analyze a psychiatric disorder experienced by the main character and several other supporting characters in a novel entitled “First Love” (2017) by Gwendoline Riley. As a guide in this study, the author uses the psychoanalytic theory initiated by Sigmund Freud about human personality in his book ‘A General Introduction to Psychoanalysis’ (1916). This study uses qualitative research methods to analyze the elements in literary works, which are then described with supporting theories. The step taken by the writer to identify the psychological problems of the characters is to describe the symptoms that arise, such as thinking about flashbacks of traumatic experiences, excessive fear, and physical attacks, which are then observed in how the characters struggle through them. The results of this study indicate that past trauma that is not appropriately handled by the characters causes a mental illness called PTSD. This study also provides an overview of how the characters use their defenses when symptoms of psychiatric disorders appear. Through sentence analysis and dialogue between characters in the novel “First Love” (2017), which is used as the object of this study, they provide an overview of what the mental illness PTSD is like and the defenses used to fight against this mental illness. Keywords: Post-traumatic stress disorder, Sigmund Freud, Novel analysis, Psychoanalysis of novel’s character, and Symptoms of PTSD.